Heterogeneous Photocatalytic Radical Synthesis of Aryl Allyl Sulfones - Wang, Liang; Zhang, Ling-feng (Synlett, 2022)
A photocatalytic synthesis of aryl allyl sulfones by a radical cascade reaction from an aryl diazonium salt, DABCO·(SO2)2 and 3-bromoprop-1-ene has been developed. This reaction employed DABCO·(SO2)2 as the SO2 source and a polyaniline–graphitic carbon nitride–titanium dioxide composite as the photocatalyst. A series of substrates were tolerated, providing the corresponding products in good yields. Moreover, the photocatalyst could be readily recovered and reused several times with only a slight decrease in its catalytic activity.
Keywords: photocatalysis; heterogeneous catalysis; semiconductor catalyst; radical cascade reaction; aryl allyl sulfones